PENGARUH MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION(RME) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV MI ISLAMIYAH KEDALEMAN ROGOJAMPI - Diah Galuh Kusumawati; Nur Wiarsih; Meliantina Meliantina (PGMI Department of Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia, 2022)
This study aims to determine the influence of the application of the Realistic Mathematic Education learning model on the mathematics learning outcomes of grade IV MI Islamiyah kedaleman Rogojampi students. This type of research is Pre-Experimental Design with a one group pretest posttest design model. The study sample was selected using cluster sampling (area sampling). The sample taken was 28 students. The data collection process uses three ways, namely observation, tests, and documentation. The data were analyzed using descriptive statistical analysis techniques and inferential analysis (prerequisite test and t-test). The results showed that students' scores before using the Realistic Mathematic Education learning model were relatively low, in contrast to after using the Realistic Mathematic Education learning model, students' scores were relatively high. Realistic Mathematic Education learning models affect student learning outcomes. This is evidenced from the results of the t-test analysis in class IV and obtained the probability of a sig(2-tailed) value of 0.000 < 0.05. Based on the results of the analysis and discussion, there was a difference in the average score in the final measurement of the pretest value, which was 59.07 increased to 74.71 (posttest average). Hypothesis testing obtained a sig value (2-tailed) is 0.000 then a sig value of < 0.05 is obtained, namely 0.000 < 0.05, and a t_hitung value of -8.295 is obtained so that the > value is -8.295 > 2.052 thus accepted and rejected. So that the results of the study can be concluded that the use of the Realistic Mathematic Education (RME) learning model affects the mathematics learning outcomes of grade IV MI Islamiyah Kedaleman Rogojampi students.